2020
DOI: 10.1002/aur.2371
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Changes in Daily Activity in Transition‐Age Autistic Youth

Abstract: Transitioning into adulthood is fraught with challenges for autistic youth. A greater understanding of the facilitators of community involvement in school and employment during this period is warranted. The current study examines changes in service need and receipt, and the stability of accessing daily structured activities, for autistic young adults over their transition period compared to adolescents and adults that did not enter the transition period. Baseline caregiver survey data were taken from the Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Autistic adolescents in C4 tended to show comparable levels of home participation and social participation at school to typically developing peers as reported by other studies (Egilson et al., 2018 ; Fogel et al., 2021 ). These findings indicate that at least a subpopulation of Autistic people who follow more adaptive pathways actively participate in a variety of daily activities across settings in adolescence, which may be connected to their functional independence and successful transitions to adulthood (Myers et al., 2015 ; Weiss et al., 2021 ). However, additional support or adaptation may be needed in less structured or unfamiliar settings (e.g., community) to ensure person‐environment fit that potentiates Autistic people's participation in various aspects of life, considering their individual strengths and needs (Chen et al., 2023 ; Lai et al., 2020 ; Szatmari et al., 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…Autistic adolescents in C4 tended to show comparable levels of home participation and social participation at school to typically developing peers as reported by other studies (Egilson et al., 2018 ; Fogel et al., 2021 ). These findings indicate that at least a subpopulation of Autistic people who follow more adaptive pathways actively participate in a variety of daily activities across settings in adolescence, which may be connected to their functional independence and successful transitions to adulthood (Myers et al., 2015 ; Weiss et al., 2021 ). However, additional support or adaptation may be needed in less structured or unfamiliar settings (e.g., community) to ensure person‐environment fit that potentiates Autistic people's participation in various aspects of life, considering their individual strengths and needs (Chen et al., 2023 ; Lai et al., 2020 ; Szatmari et al., 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…A previous study of autistic children reported stable participation in home activities but reduced participation in social and physical activities at school as children transitioned into adolescence ( Simpson et al, 2019 ). In another recent study in which a large group of autistic youth and adults was tracked over 3 years ( Weiss et al, 2021 ), a decline in participation in structured weekday activities for at least 25% of those who were recruited during the transition period was observed. This resonates with another longitudinal finding that about half of the autistic young adults no longer engaged in education- or work-related activities following high school exit ( Taylor & DaWalt, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…Regular involvement in a variety of daily activities also has the potential to ameliorate the impact of perceived stress on satisfaction with life and to facilitate socio-emotional adjustment ( Bishop-Fitzpatrick et al, 2017 ; Bohnert et al, 2019 ; Howells et al, 2019 ). The extent to which autistic youth integrate into their communities through daily activity participation reflects their strengths and needs and can be an important indicator of successful transition into adulthood ( Clark & Adams, 2020 ; Lounds Taylor et al, 2017 ; Myers et al, 2015 ; Weiss et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%